Java EE 8 Recipes A Problem-Solution Approach - Juneau, Josh (Apress, 2018)
Quickly find solutions to dozens of common programming problems with the Java Enterprise Edition Platform for small business web applications, enterprise database applications, and microservices solutions. Content is presented in the popular problem-solution format. Look up the programming problem that you want to solve. Read the solution. Apply the solution directly in your own code. Problem solved! Java EE 8 Recipes provides you with effective and proven solutions that can be used to accomplish just about any task that you may encounter. You can feel confident using the reliable solutions that are demonstrated in this book in your personal or corporate environment. Java is a mature programming language that has been refined over the years into a productive and lucrative language for those with the skills to wield it. One result of this years-long refining process is that that the language carries forward many older feature sets that no longer represent the best way of getting work accomplished. You can rest assured that Java EE 8 Recipes provides solutions using the most current approaches implemented in the most current Java Enterprise technologies, including JSON-P 1.1, JSF 2.3, and JAX-RS 2.1. Build a streamlined and reliable application that uses the latest in Java technologies, and develop it much faster than you did with the older technologies. Rejuvenate your Java expertise to use the freshest capabilities, or perhaps learn Java Enterprise development for the first time and discover one of the most widely used and most powerful technologies available for application development today. Develop productively. Develop with proven technology. Develop with Java Enterprise Edition. The book: Teaches how to develop RESTful enterprise applications quickly using the most current Java EE technologies Explores different solutions for developing sophisticated web user interfaces Walks you through a myriad of different concepts to apply while working with databases using Java technologies What You'll Learn: Develop Java Enterprise applications using the latest in Java EE technologies Build great-looking user interfaces using Java Server Faces Employ Java Servlet technology and standard frameworks in developing professional web applications Create enterprise-level database applications using Enterprise Java Beans and JAX-RS RESTFul web services Make use of Arquillian to build a cohesive test suite for Java EE applications Manage Java EE application security through Java EE's container feature set.